Expenditure Rules : Effective Tools for Sound Fiscal Policy? - Cordes, Till (IMF Working Papers; Working Paper, 2015)
This paper provides new evidence on the effectiveness of expenditure rules. The analysis is based on a unique dataset covering all countries with national and supranational fiscal rules, including 33 expenditure rules, between 1985 and 2013. It contributes to the existing literature on fiscal rules in two main ways. First, it is the most comprehensive assessment of compliance with rules and of the potential role of expenditure rules, in particular regarding long-term sustainability. Second, it analyzes whether expenditure rules are associated with changes in public investment and its efficiency.